2010
DOI: 10.1016/j.vetimm.2009.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology of feline immunodeficiency virus in the domestic cat (Felis catus)

Abstract: Studying the evolutionary mechanisms of feline immunodeficiency virus in the domestic cat (Felis catus), FIV Fca , provides a good comparison to other lentiviruses, such as HIV and FIV Pco in the cougar (Puma concolor). We review the current epidemiological and evolutionary findings of FIV Fca ,. In addition to the five accepted FIV Fca , subtypes, several recent phylogenetic studies have found strains that form separate clades, indicative of novel subtypes. In New Zealand cats, these strains of unknown subtyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
1
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 67 publications
0
25
1
4
Order By: Relevance
“…Differences in the ecology and immunology of host species (e.g., cat versus primate versus human) may be important drivers of intra-individual evolution rates (21,23). Dual infection or coinfection status may accelerate mutation rates versus those in single infections by altering the immune landscape during infection (18).…”
Section: Discussionmentioning
confidence: 99%
“…Differences in the ecology and immunology of host species (e.g., cat versus primate versus human) may be important drivers of intra-individual evolution rates (21,23). Dual infection or coinfection status may accelerate mutation rates versus those in single infections by altering the immune landscape during infection (18).…”
Section: Discussionmentioning
confidence: 99%
“…This relatively poor sensitivity might be as a result of the very low levels of provirus that can be present in infected cats, particularly in apparently healthy animals, but can also be due to variability in the proviral genome of the FIV; there can be up to 26% polymorphism between serotypes in the env and gag [30, 31]. Further, recombination with sometimes complex patterns resulting from co-infections or super-infections is also not uncommon in the FIVs [9, 32]. Because of the wide range of subtypes of FIVs and their high evolutionary rate, it is difficult to develop a PCR that is generic enough to amplify all subtypes and yet maintain high sensitivity [33].…”
Section: Discussionmentioning
confidence: 99%
“…The subtype A FIV strains are often neurotrophic and can produce neurological signs, most commonly behavioral changes but also seizures, paresis, multifocal motor abnormalities, impaired learning and disrupted sleep patterns [5]. Currently there is only one registered FIV vaccine which is composed of two FIV subtypes, A and D. The vaccine is reported to confer protection against subtypes A, B and D and might then be useful in mainland China where [32, 39], to the best of our knowledge, vaccination is seldom if ever performed. A recent study, however, has shown the vaccine does not confer solid protection and breakthroughs were found with FIV subtypes A, F, A/F and D/F [40].…”
Section: Discussionmentioning
confidence: 99%
“…The five major subtypes (clades) of FIV are designated A through E, and each has a particular geographic distribution throughout the world [30]. FIV is similar to HIV in genome structure and immunopathogenesis [31,32], and has been utilized as the only naturally-occurring animal model of immunodeficiency for HIV-infection in people [33].…”
Section: Reviewmentioning
confidence: 99%